Research on the influence of rolling element geometry on the wear resistance of drilling equipment bearings - Makovkin, O.M.; Dykha, O.V.; Valchuk, I.K.; Kalaczynski, T. (Problems of Tribology, 2025)
The article presents the results of experimental studies of the influence of the geometric parameters of rollers and raceways on the resistance of roller bearings to rolling element rotation and jamming. Failure of bearing assemblies due to roller rotation is a common cause of emergency equipment shutdown, which is accompanied by expensive repairs. The aim of the work was to determine the optimal ratio of roller length to its diameter (l/d) and the influence of raceway diameter (D) on critical wear, which leads to loss of roller stability. The research methodology was based on mathematical experimental design with variation of parameters l, d and D in laboratory conditions when simulating misalignment of the bearing assembly. An empirical relationship was established that quantitatively describes the relationship between roller geometry, raceway diameter and critical wear. The results showed that increasing l/d increases the resistance of the rollers to turning, while an excessive increase in D contributes to the growth of backlash and distortions. The most effective configuration was found to be the one with the maximum length and minimum diameter of the roller at a small value of D. The results obtained can be used for the design improvement of bearing assemblies, in particular in drilling equipment, in order to increase the resource and reliability of their operation